Survival Analysis of Patients with Chronic Kidney Disease at Dr Achmad Darwis Regional General Hospital Using the Kaplan-Meier Method - Mei Syarah Anis; Devni Prima Sari (Universitas Negeri Padang, 2025)
Abstract. Chronic kidney disease (CKD) is a global health problem with a steadily increasing incidence. In West Sumatra, its prevalence is recorded at 0.2%, with the highest proportion occurring in individuals aged 45–54 years. Although relatively low, CKD still has a substantial impact on patients' quality of life. To date, data on the survival probability of CKD patients at the regional level, particularly in the district where this study was conducted, remain limited and require further investigation. This study aims to determine the overall survival probability of CKD patients and to examine the factors that influence survival, such as age, sex, disease stage, history of diabetes mellitus, hypertension, anaemia, heart disease, and smoking. This study employs survival analysis using the Kaplan-Meier method and the log-rank test to compare differences between groups. The results show that the overall survival probability of the 140 patients declined significantly over the four-year observation period. The Kaplan-Meier analysis revealed a sharp decline in survival probability within the first 12 days of treatment, with only 20.9% of patients remaining alive by day 12. Based on the log-rank test, the factors significantly associated with survival were age, history of diabetes mellitus, hypertension, and heart disease. These findings underscore the importance of early detection and integrated management of comorbidities in clinical practice, as they may help improve survival outcomes and guide healthcare planning for CKD patients in regional settings.